Quantitative parameters of gladiolus stems according to planting dates in a subtropical environment - Schwab, Natalia Teixeira; Streck, Nereu Augusto; Ribeiro, Bruna San Martin Rolim; Becker, Camila Coelho; Langner, Josana Andreia; Uhlmann, Lilian Osmari; Ribas, Giovana Ghisleni (Pesquisa Agropecuaria Brasileira, 2015)
The objective of this work was to determine the growing seasons, in a subtropical environment, when it is possible to produce gladiolus (Gladiolus x grandiflorus) stems that meet commercial, quantitative standards for cut flowers of the national market. Two field experiments were carried out – one from August 2011 to July 2012, and the other from August 2012 to July 2013 – with three gladiolus cultivars and 12 planting dates for each experiment. Stem total length, rachis length, and stem diameter were evaluated at the harvesting point, when the petal color appears in the first three florets at the stem base. The best months for production of gladiolus stems are July, August, September, February, March, and April, although in the other planting dates the stem quality was never below the minimum standard (except for the periods of frost during heading).
Keywords: Gladiolus x grandiflorus; growing season; floriculture; commercial standard; quality